Wages and additional labour costs: An international comparison - Heinz Salowski (Intereconomics, 1980)
The international competitiveness of German industry, so greatly dependent on exports, is in large measure determined by the level of its labour costs in relation to those of its competitors in the world market, as its spokesmen never tire of pointing out. Dr. Salowski undertakes here an international comparison.
Keywords: 330